Николай Алексеевич Богомолов (16.12.1950—20.11.2020) [In memoriam: Nikolai Alekseevich Bogomolov (December 16, 1950 – November 20, 2020)] - Sobolev, Alexander (Slavica Revalensia, 2020)
This is a slightly revised republication of the obituary for a distinguished student of the literature of Russian modernism, an editorial board member of Slavica Revalensia, Prof. Nikolai Bogomolov of Moscow State University, originally published by Alexander Sobolev in his blog on November 22, 2020 (see: https://lucas-v-leyden.livejournal.com/301380.html).